Erosion‐initiated stromatolite and thrombolite formation in a present‐day coastal sabkha setting. Issue 1 (7th September 2020) - Paul, Andreas; Lokier, Stephen W.; Sherry, Angela; Andrade, Luiza Lessa; Court, Wesley M.; van der Land, Cees; Dutton, Kirsten E.; Head, Ian M.
Abstract: Laminated microbial mats and microbialites have been documented from a variety of coastal marine environments. This study aims to provide the first detailed descriptions of intertidal pools, along with their hosted thrombolite and stromatolite structures, from Abu Dhabi, and to propose a model for their formation and evolution. It is proposed that the development of pools within the upper intertidal zone was initiated by localized erosion of the laminated microbial mats during high energy events. The removal of the protective mats permitted erosion of the underlying unconsolidated sediment to produce erosional scours that continued to develop to create the pools observed today. The margins of the newly‐created submerged environment were colonized by a cyanobacteria dominated microbial community. The precipitation of aragonite cement, associated with the cyanobacteria, stabilized the pool walls and cemented the microbial communities to form stromatolitic and thrombolitic fabrics. Syndepositional cementation was further enhanced by the precipitation of marine cements as a result of evaporation‐driven Ca 2+ and Mg 2+ supersaturation. Erosion behind and below the cemented pool wall eventually resulted in rim‐collapse and the formation of the observed pool margin parallel thrombolite bands. Successive generations of lithification and erosion increased the area of the pool with the earliest thrombolites eroding and becoming increasingly isolated. In summary, the resultant microbialites developed through the complex interplay of erosion, abiotic early lithification and microbially‐mediated processes, and represent a continuum between unlithified laminated microbial mats and domal microbialites. These features are most likely produced during a sea‐level scenario of stillstand or transgression and, as such, may be useful as a diagnostic tool to elucidate the onset of transgression. The newly proposed model for stromatolite formation has significant implications for the recognition and interpretation of similar structures observed in the fossil record.